简答题:(1)因式分解:4ab-a^2+1-4b^2(2)计算:(-2b^3分之a^2)^3除以4b^2分之3a^4(3)计算:x^-1加上y^-1分之x^-2减去y^-2乘以x^-1减去y^-1分之(xy)^-2(4)x-1分之2x+x+3分之1-(x^2+2x-3)分之3x+5

来源:学生作业帮助网 编辑:作业帮 时间:2022/12/01 08:39:18
简答题:(1)因式分解:4ab-a^2+1-4b^2(2)计算:(-2b^3分之a^2)^3除以4b^2分之3a^4(3)计算:x^-1加上y^-1分之x^-2减去y^-2乘以x^-1减去y^-1分之(xy)^-2(4)x-1分之2x+x+3分之1-(x^2+2x-3)分之3x+5

简答题:(1)因式分解:4ab-a^2+1-4b^2(2)计算:(-2b^3分之a^2)^3除以4b^2分之3a^4(3)计算:x^-1加上y^-1分之x^-2减去y^-2乘以x^-1减去y^-1分之(xy)^-2(4)x-1分之2x+x+3分之1-(x^2+2x-3)分之3x+5
简答题:(1)因式分解:4ab-a^2+1-4b^2
(2)计算:(-2b^3分之a^2)^3除以4b^2分之3a^4(3)计算:x^-1加上y^-1分之x^-2减去y^-2乘以x^-1减去y^-1分之(xy)^-2
(4)x-1分之2x+x+3分之1-(x^2+2x-3)分之3x+5

简答题:(1)因式分解:4ab-a^2+1-4b^2(2)计算:(-2b^3分之a^2)^3除以4b^2分之3a^4(3)计算:x^-1加上y^-1分之x^-2减去y^-2乘以x^-1减去y^-1分之(xy)^-2(4)x-1分之2x+x+3分之1-(x^2+2x-3)分之3x+5
(1)4ab-a^2+1-4b^2=1-(a²-4ab+4b²)=1-(a-2b)²=(1+a-2b)(1-a+2b)
(2)(-2b^3分之a^2)^3除以4b^2分之3a^4
=-8b^6分之a^6×3a^4分之4b^2
=-6b^4分之a^2
(3)计算:x^-1加上y^-1分之x^-2减去y^-2乘以x^-1减去y^-1分之(xy)^-2
=(x^-1+y^-1)×(x^-1减去y^-1)分之x^-2减去y^-2乘以(xy)^-2
=(x^-2-y^-2)分之(x^-2-y^-2)乘以(xy)^-2
=(xy)^-2